Role of Najm Al_Din Ayyub in Preparing Salah Al_Din for the establishment of The Ayyubid State in Egypt - حميدوش نسرين; وفاء جوني (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
This research deals with the stages that the Ayyubid state went through since the departure of Najm al-Din Ayyub and Asad al_Din Shirkuh from Tikrit, their arrival to Al_Mosul and their meeting with its owner Imad al_Din Zinki and what resulted out of this meeting in the growth of the idea of independence in their thoughts which crystallized after their arrival to Damascus and their entry into the service of Nour Al_Din Mahmoud. The research talked specifically about how Najm Al-Din Ayyub was satisfied and accepted the participant of his son in his uncle Shirkuh’s three campaigns , which required dicussing the facilities provided by Shirkuh and the support that Salah Al_Din received from his father and auncle and his going to Egypt in addition to taking over the Ministry, waiting for the appropriate time to announce the establishment of their state in public .This matter led to the empowerment of Salah Al-Din in Egypt and the establishment of the state according to Strong foundation, so they can announce the Ayyubid state in Egypt by the hands of Salah Al-Din and annex Damascus to it after a short time.